2021
DOI: 10.1016/j.jmig.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future: Schauta-Amreich Radical Vaginal Hysterectomy Assisted by Laparoscopy with Sentinel Lymph Node Biopsy for Early-stage Cervical Cancer

Abstract: The popularity of laparoscopy to perform radical hysterectomy has massively increased over the last 2 decades. However, oncologic outcomes (overall and disease-free survival) have been found to be better in patients managed by laparotomy compared with laparoscopy, challenging this surgical route. Compared with laparotomy, vaginal access reduces postoperative morbidity, while avoiding potential cancer spread associated with laparoscopy. We describe the procedure of Schauta-Amreich radical vaginal hysterectomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Moreover, the regularity of lymphatic drainage in patients with cervical cancer and main transfer path of the disease (lymphatic metastasis) provides a theoretical feasibility of SLNB in the diagnosis and treatment of cervical cancer. Relevant studies abroad have confirmed that the detection rate of SLN in cervical cancer is as high as 90%-100%, that the sensitivity can reach 80%-100%, and that the false-negative rate is less than 10% [15,16]. Our results showed that the detection rate of SLN in 59 cervical cancer patients was 94.92%, the rate of lymph node metastasis was 25.42%, the sensitivity of SLNB was 86.67%, and the false-negative rate was 13.33%, which was consistent with the results of previous studies, indicating that SLNB is in the cervical It has high application value and high sensitivity in the diagnosis and evaluation of cancer lymph node metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the regularity of lymphatic drainage in patients with cervical cancer and main transfer path of the disease (lymphatic metastasis) provides a theoretical feasibility of SLNB in the diagnosis and treatment of cervical cancer. Relevant studies abroad have confirmed that the detection rate of SLN in cervical cancer is as high as 90%-100%, that the sensitivity can reach 80%-100%, and that the false-negative rate is less than 10% [15,16]. Our results showed that the detection rate of SLN in 59 cervical cancer patients was 94.92%, the rate of lymph node metastasis was 25.42%, the sensitivity of SLNB was 86.67%, and the false-negative rate was 13.33%, which was consistent with the results of previous studies, indicating that SLNB is in the cervical It has high application value and high sensitivity in the diagnosis and evaluation of cancer lymph node metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…After years of training in laparoscopic radical hysterectomy we had go backwards and start learning the open way of surgery again. 2 This is an educational video showing a combination of strategies and surgical approaches in patients with cervical cancer after the LACC trial Since we already have the laparoscopic platform for sentinel lymph node mapping with indocyanine green, we decided to start surgeries with minimally invasive surgery. After cervical injection of indocyanine green, we search for the bilateral sentinel lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018 the results of an early termination of the LACC trial were published,1 followed by several retrospective trials, all showing inferior outcomes of patients with cervical cancer who underwent minimally invasive surgery. After years of training in laparoscopic radical hysterectomy we had go backwards and start learning the open way of surgery again 2…”
Section: Discussionmentioning
confidence: 99%